2006
DOI: 10.4049/jimmunol.176.11.6586
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+Foxp3+ T Cells and CD4+CD25−Foxp3+ T Cells in Aged Mice

Abstract: Aging is associated with a progressive decline in T cell-mediated immune responses. However, it has been unknown whether regulatory/suppressive CD4 T cells are involved in this decline. Our in vitro analyses revealed that CD4+CD25+ T cells, the well-characterized naturally occurring regulatory/suppressive CD4 T cells, in aged mice are functionally comparable to those in young mice (i.e., anergic and suppressive), although slightly increased in number. In contrast, functional changes to whole CD4+CD25− T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
162
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(193 citation statements)
references
References 31 publications
31
162
0
Order By: Relevance
“…2D) ϩ T cells increases with age (19). The reasons for this increase are unknown but could involve processes similar to those described above, such that some Foxp3 Ϫ T cells are deleted from the repertoire due to reactivity to selfAg, whereas Foxp3 ϩ T cells are spared from deletion to increase in prevalence over time.…”
Section: Foxp3mentioning
confidence: 95%
“…2D) ϩ T cells increases with age (19). The reasons for this increase are unknown but could involve processes similar to those described above, such that some Foxp3 Ϫ T cells are deleted from the repertoire due to reactivity to selfAg, whereas Foxp3 ϩ T cells are spared from deletion to increase in prevalence over time.…”
Section: Foxp3mentioning
confidence: 95%
“…Regulatory T cells were shown to accumulate with aging contributing to decrease immune responses. However the augmentation of suppressive function is not due to CD4 + CD25 + Foxp3 + T cells but to CD4 + CD25 -Foxp3+ T cells that appear with aging (Nishioka, Shimizu et al 2006). Since a lack of IL-2 secretion is reported in old individuals, with deficiency in CD4 help, IL-2 treatments were assessed and shown to increase Treg cell numbers in lymphopenic individuals (Zhang, Chua et al 2005).…”
Section: Prevention Of Aging and Immunodepressionmentioning
confidence: 99%
“…We found that aged BWF1 mice had substantially increased frequency (Figure 1A) and number ( Figure 1B) of Foxp3 ϩ CD4 ϩ T cells in the lymphoid organs compared with young BWF1 mice. A recent study has shown an age-dependent increase in CD25 Ϫ Foxp3 ϩ CD4 ϩ T cells in 24-month-old normal mice, 25 but increased Foxp3 ϩ CD4 ϩ T cells in aged BWF1 mice was not merely an age-dependent event be- (Figure 2A), CD25 ϩ CD4 ϩ T cells isolated from the spleen and lymph nodes of both young and aged BWF1 mice did not proliferate on stimulation ( Figure 2B) and showed suppressive activity ( Figure 2C). Furthermore, CD25 ϩ CD4 ϩ T cells isolated from the kidney ( Figure 2C) and lung (data not shown), ie, the target organs, of aged BWF1 mice also showed suppressive activity comparable to those from the spleen and lymph nodes.…”
Section: Increased Number and Frequency Of T Reg Cells In Aged Bwf1 Micementioning
confidence: 99%